Implementation of Generalized Variance and T2- Hotelling Control Charts for Monitoring the Water Quality Characteristics at the Perumda Air Minum Tugu Tirta Kota Malang - Dini, Karina Rahmah; Fitrah, Evelin Nuga; Rozi, Fachrur (Proceedings of the International Conference on Green Technology, 2026)
Water is one of the most important needs for humans, so it is necessary to ensure the quality of drinking water that is suitable for consumption according to the standards of the Ministry of Health. This study aims to analyze the quality of water produced by Perumda Air Minum Tugu Tirta Kota Malang using the Statistical Process Control (SPC) method, namely the Generalized Variance and -Hotelling control charts. This quantitative research uses secondary data from September 2023 to June 2024 with turbidity, residual chlor, and pH parameters. This study analyzed in two phases, Phase I and Phase II. The normality assumption test and correlation between variables were carried out before making the control chart. The results showed that in Phase I, the Generalized Variance and -Hotelling charts detected several observation points outside the control limits. However, after revision, the data showed a statistically controlled condition. In Phase II, the Generalized Variance graph showed in control and relatively stable process, while the -Hotelling graph showed two points out of the control limits. The conclusion of this study is that quality control using the multivariate method is able to detect process uncontrollability effectively, and the quality of produced water generally satisfy the standards for consumption.